Vertebral uptake of 99mTc-macroaggregated albumin during lung perfusion scanning - D´Abadie, Philippe; Ghaye, Benoit; Jamar, François (World Journal of Nuclear Medicine, 2020)
A 53-year-old female underwent a lung ventilation/perfusion scintigraphy (V/Q scan) in the workup of extensive thrombosis of the left subclavian and internal jugular veins. The perfusion lung scan visualized an atypical uptake in the thoracic vertebrae. A chest Computed Tomography (CT) scan demonstrated unusual tortuous and opacified thoracic superficial veins, collaterals of the lateral thoracic vein. Many venous collateral pathways can be developed in the case of superior vena cava syndrome.99mTc-macroaggregated albumin particles may pass through the lateral thoracic vein and eventually through the vertebral venous plexus before being finally trapped by the vertebral capillaries. Besides right-to-left shunting, extrapulmonary uptake in the lung perfusion scintigraphy is very rare and may be used by collateral venous pathways.
Keywords: Collateral pathways; lung perfusion scan; superior vena cava syndrome; vertebral uptake